ChemInform Abstract: Ruthenium Hydride‐Promoted Dienyl Isomerization: Access to Highly Substituted 1, 3‐Dienes. Issue 33 (25th July 2013) - Clark, Joseph R.; Griffiths, Justin R.; Diver, Steven T.
Abstract Ruthenium hydrides are found to promote the positional isomerization of 1, 3‐dienes into more highly substituted 1, 3‐dienes in a stereoconvergent manner.